2016
DOI: 10.1080/09540121.2016.1173642
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood community characteristics associated with HIV disease outcomes in a cohort of urban women living with HIV

Abstract: Recent studies have found geographic variations in immune and viral HIV disease outcomes associated with Census measures of neighborhood poverty and segregation. Although readily available, such aggregate Census measures are not based on health behavior models and provide limited information regarding neighborhood effect pathways. In contrast, survey-based measures can capture specific aspects of neighborhood disadvantage that may better inform community-based interventions. Therefore, the aim of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…Our finding is inconsistent with one study of New York City surveillance data which suggested that while neighborhood poverty was not associated with achieving viral suppression, it was associated with lower likelihood of maintaining viral suppression after diagnosis [33]. However, the literature on the effect of neighborhoods on viral suppression is mixed with some studies showing an association between residing in areas of high deprivation and poor viral suppression [34,35], and others showing no association [36,37]. It is possible that neighborhood units smaller than the ZIP code or other neighborhood characteristics not measured in this study, particularly perceptions of one's neighborhood, may be important.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding is inconsistent with one study of New York City surveillance data which suggested that while neighborhood poverty was not associated with achieving viral suppression, it was associated with lower likelihood of maintaining viral suppression after diagnosis [33]. However, the literature on the effect of neighborhoods on viral suppression is mixed with some studies showing an association between residing in areas of high deprivation and poor viral suppression [34,35], and others showing no association [36,37]. It is possible that neighborhood units smaller than the ZIP code or other neighborhood characteristics not measured in this study, particularly perceptions of one's neighborhood, may be important.…”
Section: Discussioncontrasting
confidence: 99%
“…Characteristics of men who have sex with men by sustained viral load suppression, 2017 (n = 3386) Characteristics of men who have sex with men by sustained viral load suppression, 2017 (n = 3386) (Continued)In the multivariate analyses the odds of sustained viral suppression were lower for younger MSM (18-24 [aOR 0.51, 95% CI 0.34-0.77] and 25-34 [aOR 0.68, 95% CI 0.52-0.87] compared with[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] year-olds) and for Black MSM compared with White MSM (aOR 0.44, 95% CI 0.29-0.69) (Table 2). Individuals not enrolled in the ACA (aOR 0.66, 95% CI 0.48-0.90), currently reporting Characteristics of men who have sex with men by sustained viral load suppression, 2017 (n = 3386) (Continued)…”
mentioning
confidence: 99%
“…Meanwhile, studies in Chicago, St. Louis, and Florida found no neighborhood characteristic associations with viral suppression (Burke-Miller et al, 2016; Shacham, Lian, Onen, Donovan, & Overton, 2013; Shacham, Lopez, Onen, & Overton, 2017; Sheehan, Fennie, Mauck, Maddox, Lieb, & Trepka, 2015). These more recent analyses generally agree with our own study findings, though only Sheehan et al explicitly evaluated retention in care, finding a null association for that outcome as well.…”
Section: Discussionmentioning
confidence: 98%
“…3 An emerging line of multilevel research suggests that neighbourhood factors shape HIV care and treatment among HIV-infected populations: neighbourhood disadvantage is associated with lower CD4 counts and less ART initiation. 2829 …”
Section: Discussionmentioning
confidence: 99%